Efektivitas Sanksi Pidana terhadap Pelaku Kejahatan Lingkungan Hidup - Heriyanto Heriyanto; Akhmad Wira; Qorib Qorib; Chaidir T. Karim; A. Kamil Rajak (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Indonesian Constitution provides an ontological guarantee for the right to a healthy environment, yet continuous economic extractivism paradigms have catalyzed massive, structural ecological crimes. Specifically, environmental criminal enforcement is severely subordinated to administrative regimes (ultimum remedium), allowing mega-corporations to calculatively reduce judicial fines to mere additional operational costs, which culminates in sentencing disparities and rampant ecological recidivism. Preceding scholarly literature remains heavily fragmented, analyzing penal disproportionality or evidentiary procedural limitations in isolation, thereby leaving a distinct gap in holistic synthesis concerning the new National Criminal Code and transnational zemiological frameworks. This doctrinal legal research aims to dissect the systemic dysfunctions within corporate environmental criminal enforcement and reconstruct a prescriptive, robust penal policy architecture. The normative analysis demonstrates that the paralysis of deterrence is deeply rooted in severe penal proportionality deficits, the manipulation of the corporate veil, and the rigid application of the in dubio pro reo maxim, which actively facilitates corporate impunity under the guise of scientific uncertainty. As a conceptual novelty, this article proposes the statutory integration of the in dubio pro natura principle and the harmonization of autonomous environmental crime doctrines—derived from European Union Directives—into the purview of the 2023 National Criminal Code.